(untitled) - Schwarz, Edward A. (Tokyo, 1974)
This book is more than an illustrated dictionary of Japanese terms. It is also a phrase book of useful Japanese for foreigners. This book consists of the following three parts: getting around Japan, only in Japan, living in Japan.
Keywords: Japanese language,Social life and customs; Conversation and phrase books; Japan